Urbanization and the South Asian enigma: A case study of India - Basudeb Guha-Khasnobis; K. S. James (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
South Asia has the highest rate of child malnutrition in the world, despite rapid economic growth compared to other regions such as sub-Saharan Africa. Known as the 'South Asian enigma' this feature is partly attributed to the low status of women in South Asian societies. This paper examines this tenet in the context of India, with particular emphasis on possible differences between rural and urban scenarios. The empirical evidence reveals some important differences, which are relevant for policies relating to women's empowerment against a backdrop of rapid urbanization.
Keywords: D1; I11; R0; 330; urbanization; women; malnutrition; slums; India